Evaluation of the learning curve for robotic single-anastomosis duodenal–ileal bypass with sleeve gastrectomy - Wang, Lun; Yu, Yang; Wang, Jinfa; Li, Shixing; Jiang, Tao (Frontiers in Surgery, 2022)
Background The robotic surgical system is being used in various bariatric procedures.However,only a few studies with very small sample size are present on robotic single-anastomosis duodenal–ileal bypass with sleeve gastrectomy (SADI-S).Moreover,to date,the literature on learning curve of robotic SADI-S is completely lacking. Objective This retrospective study aimed to estimate the learning curve of robotic SADI-S. Methods 102 consecutive patients who underwent robotic SADI-S between March 2020 and December 2021 were included. Textbook outcome standard was performed to comprehensively evaluate clinical outcome of robotic SADI-S. Based on the textbook outcome, we evaluated the learning curve of robotic SADI-S by the cumulative sum (CUSUM) method. Results The mean operative time was 186.13±36.91 min.No conversion to laparotomy or deaths occurred during the study period. The rate of complications was 6.9% (n=7),of which major complications were identified in 2.9% (n=3),including 2 gastric leakages and 1 respiratory failure.A total of 60 patients reached the textbook outcome standard. The rate of textbook outcome was positive and was steadily increasing after the number of surgical cases accumulated to the 58th case.Taking the 58th case as the boundary, all the patients were divided into the learning stage group (the first 58 patients) and mastery stage group (the last 44 patients). The rate of complications,proportion of abdominal drainage tubes and postoperative hospital stay were significantly higher in the learning stage group compared with the mastery stage group(P＜0.05).No significant difference was observed between the two groups in terms of patient demographic data,operative times, reoperations and readmission. Conclusion Robotic SADI-S is a feasible and reproducible surgical technique with a learning curve of 58 cases.